Dietary Risk-Related Colorectal Cancer Burden: Estimates From 1990 to 2019 - Deng, Yujiao; Wei, Bajin; Zhai, Zhen; Zheng, Yi; Yao, Jia; Wang, Shuqian; Xiang, Dong; Hu, Jingjing; Ye, Xianghua; Yang, Si; Wu, Ying; Li, Na; et al. (Frontiers in Nutrition, 2021)
Background: Colorectal cancer remains a public health problem worldwide. Dietary risk factors play a key role in the carcinogenesis and progression of colorectal cancer. This study aimed to explore the geographical and temporal trends in various dietary factors related colorectal cancer. Methods: We extracted data from GBD 2019 study, including deaths, disability-adjusted life-years (DALYs), age-standardized rate (ASR), summary exposure value (SEV) among 4 world regions, 11 age groups, 21 regions, 204 countries and territories between 1990 and 2019. The estimated annual percentage changes (EAPCs) were calculated to evaluate the variation trend of ASRs. Results: Dietary factors were the leading cause of colorectal cancer death and DALY rate, regardless of age. Dietary factors related deaths and DALYs accounted for 32% and 34% of global colorectal cancer, respectively. Further analysis showed that low whole grains intake remained the leading cause of cancer death and DALY rate, followed by milk and calcium. Diet low in whole grains, milk and calcium accounted for 81.61% deaths and 81.64% DALYs totally. Deaths and DALYs of dietary factors related colorectal cancer grew by half from 1990 to 2019. All ASRs remained higher for males than females. Asia carried the highest colorectal cancer burden attributable to dietary risks, especially for East Asia (ASDR: EAPC=1.15, 95%CI: 0.88-1.42; DALY: EAPC= 1.08, 95%CI: 0.82-1.34). The heavier burden also existed in High-middle and middle SDI quintiles. China always had the highest deaths and DALYs of colorectal cancer attributable to dietary risks, followed by USA, India and Japan. Conclusion: Large variations existed in dietary risks related colorectal cancer burden among sexes, regions, and countries. More target interventions to address modifiable dietary risk factors would save 32% of deaths and 34% of DALYs for colorectal cancer.